Analysis of multiple organ function damage in patients with severe COVID-19 pneumonia: Organ damage indicators of COVID-19 - Feng, Shiyan; Wang, Fengxin; Cai, Zhao; Wu, Weibo; Li, Yinfeng; Chen, Li; Cao, Mengli; Peng, Ling; Jiang, Xiao; Zhang, Peiyan; Li, Jianming; Yang, Liuqing; et al. (Journal of Medical Biochemistry, 2023)
Background: This study aims to analyze the changes and significance of organ function indices in patients with severe Coronavirus Disease 2019 (COVID-19) pneumonia for prediction of major organ damages and guiding treatment schemes. Methods: 63 patients with severe COVID-19 pneumonia were selected as the severe group and 73 patients with mild syndromes were selected as the mild group. SAS9.4 software was used for statistical analysis of the data. Results: Levels of ALT, AST, cTnI, Cr, PT, APTT and D-DIC of the severe group were significantly higher while PLT was lower than those of the mild group. The data of all quantitative variables were converted into categorical variables. Significantly higher levels of AST, ALB, D-DIC and higher proportion of bilateral lung involvement were observed from the severe group comparing to those in the mild group, while the difference in the other indices between the two groups was insignificant in statistical perspective. Discussion: There are significant differences in the levels of multiple organ function indices between the severe group and the mild group of patients with COVID-19 pneumonia infection. Through examining the relevant indices, conditions of patients’ multiple organ function damage could be predicted and used as guidance of treatment.
Keywords: Severe cases; Coronavirus Disease 2019 (COVID-19) pneumonia; Organ function index